2008
DOI: 10.1002/ar.20648
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Rests of Malassez and OX6‐Immunopositive Cells in the Periodontal Ligament of Rat Molars: A Light and Transmission Electron Microscope Study

Abstract: It has been shown that human and cat epithelial cell rests of Malassez (ERM) consist of heterogeneous cell populations. Immunohistochemical and immunoelectron microscopic analyses have verified the presence of neuroendocrine and Merkel-like cells in both of these epithelia. During experimental orthodontic tooth movement, immunocompetent cells have also been found in the vicinity of ERM in rat periodontal ligament (PDL), but have not been characterized in normal rat PDL. The aim of this study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Similar findings of cytoplasmic processes extending towards the outer surface of the ME and periodontal immunocompetent cells have been reported [17,18]. This morphology resembles that of sensory epithelial cells in glandular tissue, or the intestinal lumen.…”
Section: Discussionsupporting
confidence: 75%
“…Similar findings of cytoplasmic processes extending towards the outer surface of the ME and periodontal immunocompetent cells have been reported [17,18]. This morphology resembles that of sensory epithelial cells in glandular tissue, or the intestinal lumen.…”
Section: Discussionsupporting
confidence: 75%
“…An analysis of the distribution of ED1-immunopostive cells in the PDL of first mandibular rat molars reported that they were most abundant in the tooth root bifurcation (Kan et al 2001), in the same area where large ERM cell clusters can be seen. Moreover, the same area houses DCs that have the characteristics of activated antigen-presenting cells and show cell-to-cell contact with lymphocytes (Hamamoto et al 1998;Kaneko et al 2008;Tadokoro et al 2008). In a recent study, we found that ERM were in contact with OX61 immunocompetent cells, and that OX6-immunopositive cells surrounding epithelial cells showed ultrastructural diversity, suggesting the involvement of several types of immunocompetent cells with periodontal epithelial cells (Tadokoro et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…The observation of the relation of cells immunoreactive to CK and ED1 was difficult because the immunoreaction products of ED1 were recognized only on organelles belonging to the phagolysosomal apparatus of macrophages and DCs, and did not define their shape near the root surface. On the other hand, the observation of the relationship between CK-and OX6-immunopositive cells was relatively easy, because the immunoreaction products of OX6 are recognized on the cell membrane (Kan et al 2001;Tadokoro et al 2008). It appeared that most of the OX6-immunopositive cells, which were close to or in contact with CK-immunopositive cells near cervical and furcational cementum contained few ED1 immunoreaction products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bar, 10 mm. In (C), a furcation region of a root of 45-day-old rat shows a rest of these large RM contained cells joined to each other by desmosome junctions and bundles of cytokeratin filaments in their cytoplasm, characterizing their epithelial nature (Hasegawa et al, 2003;Luan et al, 2006;Suzuki et al, 2006;Tadokoro et al, 2008). It is known that the RM are usually found in the periodontal ligament Fig.…”
Section: Discussionmentioning
confidence: 98%